Detail of the Masonic Temple at 183-186 Tremont Street, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Detail of a door leading into the Masonic Temple at 183-186 Tremont Street at Boylston Street. Masonic Temple designed by Merrill Wheelock, ca. 1865; demolished, 1899 9 1/4 x 7 1/8 Photographs